Implementasi Technopreneurship Berbasis Inkubator Bisnis Untuk Meningkatkan Sikap, Minat dan Perilaku Wirausaha - Elfizon Elfizon; Sukardi Sukardi; Aswardi Aswardi; Syamsuarnis Syamsuarnis; Salma Taqwa (JTEV (Jurnal Teknik Elektro dan Vokasional), 2022)
Student business incubators are organizational units that provide facilities and infrastructure as well as integrated services in developing new entrepreneurs so that they develop into strong and independent entrepreneurs. It is hoped that the student business incubator will have a role in driving the pace of regional and national economic growth and progress to achieve a more prosperous society. Methods for operating a student business incubator include; a) service of facilities and infrastructure in the form of offices, laboratories and workshops both on campus and in partner companies that can be shared; b) access to management training opportunities for tenants to generate, foster and develop entrepreneurs on an ongoing basis so that they become strong entrepreneurs; c) consulting services; d) establishing a working network between entrepreneurs and employers' associations; e) product development into commercial products.